El papel de las energías renovables en la matriz energética colombiana - Ramírez Fernández, René (Corporación Universitaria Americana, 2023)
Conservation is a state of harmony between Man and the Earth" is a phrase associated with Aldo Leopold (1887-1948) American environmentalist and with which I wish to approach this important work entitled "THE ROLE OF RENEWABLE ENERGIES IN THE COLOMBIAN ENERGY MATRIX" that I am honored to prologue and with whose publication the Master, Eng. René Ramírez Fernández, of notable academic experience, in his role as Coordinator and one of the authors of the book, achieves in the compilation that the researchers show their awareness for the care of the environment and their visible concern for the abuse of non-renewable energies advocating, with scientific argument, for an energy balance for Colombia, promoting an energy transition, for the use of renewable energies and the use of biodigesters for the reduction of the carbon footprint. It should be noted that each of the contributions that you will find in the book are the result of research that has had as a starting point the collection of information, the analysis of real statistical data and the use of a methodology that ensures that the conclusions that are socialized in each of the four chapters of the book are important contributions that have a scientific support.